Cauliflower mosaic virus (CaMV) Biology, Management, and Relevance to GM Plant Detection for Sustainable Organic Agriculture - Bak, Aurélie; Emerson, Joanne B. (Frontiers in Sustainable Food Systems, 2020)
In today’s global market, some organic farmers must meet regulatory requirements to demonstrate that their plants and feedstocks are genetically modified organism (GMO)-free. Many GM plants are engineered to contain a promoter from the plant virus, Cauliflower mosaic virus (CaMV), in order to facilitate expression of an engineered target gene. The relative ubiquity of this CaMV 35S promoter (P35S) in GM constructs means that assays designed to detect GM plants often target the P35S DNA sequence, but these detection assays can yield false-positives from plants that are infected by naturally-occurring CaMV or its relatives within the Caulimoviridae. This review places CaMV infection and these ambiguous GM plant detection assays in context, serving as a resource for industry professionals, regulatory bodies, and researchers at the nexus of organic farming and global commerce. We first briefly introduce GM plants from a regulatory perspective, and then we describe CaMV biology, transmission, and management practices, highlighting the relatively widespread nature of CaMV infection in both GM and non-GM crops within the Brassicaceae and Solanaceae families. Finally, we discuss current knowledge of public food safety related to the consumption of CaMV-infected produce.